The Bacillus thuringiensis vegetative insecticidal protein Vip3A lyses midgut epithelium cells of susceptible insects. - Yu, C G (1997)
The Vip3A protein is a member of a newly discovered class of vegetative insecticidal proteins with activity against a broad spectrum of lepidopteran insects. Histopathological observations indicate that Vip3A ingestion by susceptible insects such as the black cutworm (Agrotis ipsilon) and fall armyworm (Spodoptera frugiperda) causes gut paralysis at concentrations as low as 4 ng/cm2 of diet and complete lysis of gut epithelium cells resulting in larval death at concentrations above 40 ng/cm2. The European corn borer (Ostrinia nubilalis), a nonsusceptible insect, does not develop any pathology upon ingesting Vip3A. While proteolytic processing of the Vip3A protein by midgut fluids obtained from susceptible and nonsusceptible insects is comparable, in vivo immunolocalization studies show that Vip3a binding is restricted to gut cells of susceptible insects. Therefore, the insect host range for Vip3A seems to be determined by its ability to bind gut cells. These results indicate that midgut epithelium cells of susceptible insects are the primary target for the Vip3A insecticidal protein and that their subsequent lysis is the primary mechanism of lethality. Disruption of gut cells appears to be the strategy adopted by the most effective insecticidal proteins.